The Environmental Evaluation Work Group Fiscal Year 1979 Studies of the Winter Navigation Demonstration Program. Effects of Ship-Induced Waves in an Ice Environment on the St. Marys River Ecosystem - Poe, T. P.; Edsall, T. A.; Hiltunen, J. K. (1979)
A study was conducted at selected sites in the St. Marys River to provide a base of information for evaluating the effects of ship-induced, under- ice surge waves, created by vessel passage in the adjacent ice-covered navigation channel on fish, fish-food organisms, and fish habitat at those sites. This report evaluates the information developed during the study and, with other relevant materials available, renders judgements, where possible, on the effect and impact of under-ice surge waves caused by vessels on the fish, fish-food organisms, and fish habitat in the St. Marys River.